HONEY BEE FORAGERS AND SOME BEE PRODUCTS AS POTENTIAL BIOINDICATORS FOR ENVIRONMENTAL CONTAMINATION WITH HEAVY METALS - Mohammed, Nora; Naeef Ayoub , Zahra (Science Journal of University of Zakho, 2025)
Heavy metals are persistent pollutants traveling through the environment-from their industrial source into the atmosphere, soil, and water-and finally into the food chain. They pose the greatest danger to human and animals. Honey bees (Apis mellifera) are good bioindicators of environmental pollution because they accumulate heavy metals in their bodies and products, although showing no immediate effect. Bee-related samples (foragers, honey, and pollen) collected from five sites in Duhok Province in May 2025 were investigated. The assessment confirmed the presence of lead (Pb), zinc (Zn), copper (Cu), cadmium (Cd), and chromium (Cr) in varying concentrations. Pb levels varied between 0.0003 and 0.0024 mg/kg, while the greatest amount of Pb was detected in pollen. One pollen sample contained Zn levels as high as 20.365 mg/kg. Cu levels fluctuated but didn’t show significantly either across locations or sample types. Cr levels were determined to be within WHO-recommended levels, while traces of Cd and Fe were well below the safety limits. Some pollen and honey samples from L2 and L3 showed higher amounts than safety standards, but most were below the limits. The results indicate that pollen and honey are more prone to metal accumulation, confirming contamination at a much lower level